Perancangan Interior Galeri Kebaya Modern di Surabaya - Lintu tulistyantoro, Winnie Tritanjaya Wong (Intra, 2014)
Designing the interior of a gallery in the middle of the modern this is the big challenge where shall be adjusted withÂ  era development rightnow with an element of culture. Of a gallery is expected to add a reference several models kebaya, because kebaya is Indonesian asset. The concept is used to adjust a motif that is often used in kebaya has been in modification. Expected by the existence of this gallery became a place that informative for many people. To support those people, will be held a modern kebaya gallery with many facilities such as:lobby, fashion show area,exhibition,store,consultation room,and many more.